مشرق کی طربیہءِ خداوندی:جاوید نامہ: Javeed Nama:An Eastern Divine Comedy - رضوانہ نقوی,ڈاکٹر علی کمیل قزلباش (Tashkeel e Jadeed, 2023)
Javeed Name by Dr Mohammad Iqbal is a masterpiece in persian literature. It is a long poem in the form of ‘’Masnawi’’ which is comprised almost 2000 pieces of poetry. It was 1st published in 1932 and after that several additions have been published up till now. Javeed Nama infect is a fantastical travelogue leaded by Molana Room towards the beyond stars and worlds, where Iqbal tryst the souls of renowned & reputable personalities of this earthly world. In this Masnawi Iqbal has presented the various type of intellectual, religious, political and social facts and raise the questions about the men’s Identity & honour.Iqbal has called this book ‘’Divine Comedy’’ of Asia after the style of Dante’s ‘’Divine Comedy’’, the book commence with the psalm but the real motives come in front when the poet meets Molana Room by the river bank in the evening. Iqbal asks a few questions to Rumi’s soul which are answered and then poet’s and Rumi’s spirits start their travel to sky, they hear the welcome song sung by stars, then they step forward to moon and stay there for short, here they meet a World friendly man named ‘’Wishwa Mittr’’ he asks some questions to Iqbal wich are replid by him then they visit other planets and meet other personalities like Ibn_a Hallaj, Ghalib, Qurat_ul_aain and also watch sinful souls in torments. In the last part of the Book the poet addresses his son which is actually an address and message to future generations.